Perceptions of part time students (EPJJ) towards the service quality offered at UiTM Dungun, Terengganu / Zainuddin Zakaria, Faizatul Akmam Aminiddin and Moktar Awang - Zakaria, Zainuddin; Aminiddin, Faizatul Akmam; Awang, Moktar (2004)
In this new era of globalization, service quality in any industry especially in the service sectors, has become an increasingly important issue. Customers are now focused on what the company can offer and whether needs and wants can be satisfied. Usually, service quality is related to the customer satisfaction in many dimensions and aspects and somehow it is difficult to fulfill those aspects. Service quality, emphasizing consumer satisfaction, is a newly emerging field of concern. In order to attract customers, serve their needs and retain them, sendee providers and researchers are actively involved in understanding consumers’ expectations and perceptions of service quality. Service quality is a feature of the literature in marketing and operations management, but is just starting to gain attention in higher education. The educational literature suggests that there is mounting pressure from the customers of higher education, which include students, parents, alumni, employers and legislators, to close the widening gap between their expectations of institutional performance and the actual performance (Brigham, 1994). Education industry, both lower and higher education institutions cannot run away from the topic of service quality, especially where tire students (customers) are concerned. In Malaysia, this issue has a great impact to the education industry especially with the large birth of private institution. As many of the public institutions in Malaysia remain in a conservative manner, the issue of service quality may be a threat to them. Service quality is not a new issue in service industry but where the higher education institution in Malaysia is concerned, again sendee quality is a pressing subject. With many players in the higher education institutions in Malaysia, ranging from public universities to private colleges to branches of foreign universities, the competition among them is great. Nowadays, customers choose higher learning institution that can deliver more then what they expect. Therefore, quality plays the major role to differentiate them from competitors and at the same time gain competitive advantages. In view of this development, the researchers decided to engage in a study of evaluating the perceptions of the E-PJJ (Pengajian Jarak Jauh) students towards the services offered by the Education Development Center (EDC) at Universiti Teknologi MARA (UiTM), Dungun campus, Terengganu. The researchers conducted the research based on the SERVQUAL model proposed by (Parasuraman et al., 1988). The model suggested that the Service Quality of any industries consists of five dimensions, which included Tangibility, Reliability, Responsiveness, Assurance and Empathy. Based on this model, the researchers evaluated the gap between the expectations and the perceptions of the students towards the five service quality dimensions. The students’ perception is defined as their perceptions on the actual service experience received by them from the EDC at UiTM Dungun. A sample of 53 students was chosen from a total population of 77 students. Data were analysed using the SPSS software. The researcher discovered that even though there were gaps between the expectations of the students with their actual experience of receiving the service (perceptions), the majority shows a high degree of satisfaction towards the service provided by the EDC at UiTM Dungun.